The effect of combination of massage gun therapy with exercise on increasing range of motion and movement function in patients with non-specific low back pain - As Shafi, Sabda Hussain; Prasetyo, Yudik; Arjuna, Fatkurahman; Rahayu, Atikah (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Low back pain (LBP) is a musculoskeletal disorder caused by unergonomic positions. This study aimed to determine the effect of massage gun treatment and passive stretching in increasing range of motion (ROM) and joint function of non-specific LBP. The method used in this research was a quasi-experimental method with a one group pretest-posttest design, then a sampling technique was carried out using purposive sampling. The study included 20 voluntary participants (aged 20–65) with low back pain who provided informed consent. The results of the study showed that the range of motion, measured using a goniometer, increased in forward flexion, left flexion, right flexion, extension, left rotation, and right rotation in individuals with LBP. Measurements taken before treatment and after treatments 1 to 3 showed a significant increase (p=0.000, <0.05). Massage gun treatment combined with passive stretching also improved joint movement function, as measured using the Oswestry Disability Index (ODI), with pre- and post-treatment results from treatments 1 to 3 showing a significant improvement (p=0.000, <0.05). It can be concluded that massage gun therapy combined with passive stretching effectively increases the range of motion and motor function in individuals with non-specific LBP.